Women's Work and Agency in GPNS during Economic Crises: The Case of the Greek Table Grapes Export Sector. Issue 3 (3rd July 2019) - Sifaki, Eleni
ABSTRACT: The expansion of global production networks (GPNs) has shifted women's roles in agriculture worldwide. Financial and economic crises have intensified commercial pressures, leading to precariousness in women's work. This has been magnified by government austerity measures. This article combines the GPN and feminist political economy literatures to investigate how the tensions between commercial pressures and gender relations and institutions in a time of economic crisis drive precariousness in women's work and the implications for women's adaptive agency. These questions are explored through the case of the table grapes export sector in Greece. The study finds that women farmworkers went back to waged and/or unwaged work in table grapes, but the need for their skilled work enabled them to retain some agency, even as unwaged laborers.